Trade liberalization and gender inequality - Janneke Pieters (IZA World of Labor, 2018)
Women consistently work less in the labor market and earn lower wages than men. While economic empowerment of women is an important objective in itself, women's economic activity also matters as a condition for sustained economic growth. The political debate on the labor market impacts of international trade typically differentiates workers by their educational attainment or skills. Gender is a further dimension in which the impacts of trade liberalization can differ. In a globalizing world it is important to understand whether and how trade policy can contribute toward enhancing gender convergence in labor market outcomes.
Keywords: F66; J16; J2; J31; 330; trade; gender inequality; wages; employment